2011
DOI: 10.1134/s2075111711040126
|View full text |Cite
|
Sign up to set email alerts
|

Variability of morphometric characteristics of Galega orientalis Lam. In some populations of natural and secondary ranges

Abstract: It is shown that, in the invasion process, the G. orientalis phenotype has changed and differs from the natural one. The invasion phenotype is more "vigorous": the total biomass of the top plant organs, the length of inflorescences, the number of flowers, and also seed productivity are increasing. A tendency toward augmentation of some morphometric features under the increase in duration of the naturalization process is noted. The study data reveal an increase in competitive ability of G. orientalis in the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Plants of species of Galega L. are valuable perennial and productive crops with the protein-rich chemical composition of plant raw material (Baležentienė, 2008). They widespread in natural flora and are characterized by high productivity of seeds (Tkacheva, Vinogradova and Pavlova, 2011). Results obtained by Peiretti (2009) showed that G. officinalis has the potential for large-scale ensiling if plants are harvested at the budding stage or during regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Plants of species of Galega L. are valuable perennial and productive crops with the protein-rich chemical composition of plant raw material (Baležentienė, 2008). They widespread in natural flora and are characterized by high productivity of seeds (Tkacheva, Vinogradova and Pavlova, 2011). Results obtained by Peiretti (2009) showed that G. officinalis has the potential for large-scale ensiling if plants are harvested at the budding stage or during regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Galega orientalis has a competitive advantage over closely related G. officinalis L. in more numerous flowers and seeds per inflorescence, higher pollen fertility, vegetative propagation capabilities, and higher population density [ 195 ]. The main characteristic feature of Galega orientalis is its cultigeneous distribution range, far exceeding the one for G. officinalis.…”
Section: Resultsmentioning
confidence: 99%
“…Both species got high pollen fertility and germinating capacity of scarified seeds (Table 2). Galega orientalis has got competitive advantage against closely-related G. officinalis in more numerous flowers and seeds per inflorescence, higher pollen fertility, vegetative propagation capabilities and higher population density [10]. The main characteristic feature of Galega orientalis is its cultigeneous distribution range, far exceeding the one for G. officinalis.…”
Section: Resultsmentioning
confidence: 99%